Overexpression of POSTN in Tumor Stroma Is a Poor Prognostic Indicator of Colorectal Cancer - Hyeon Jeong Oh; Jeong Mo Bae; Xian-Yu Wen; Nam-Yun Cho; Jung Ho Kim; Gyeong Hoon Kang (Korean Society of Pathologists & the Korean Society for Cytopathology, 2017)
Background Tumor microenvironment has recently drawn attention in that it is related with tumor prognosis. Cancer-associated fibroblast also plays a critical role in cancer invasiveness and progression in colorectal cancers. Periostin (POSTN), originally identified to be expressed in osteoblasts and osteoblast-derived cells, is expressed in cancer-associated fibroblasts in several tissue types of cancer. Recent studies suggest an association between stromal overexpression of POSTN and poor prognosis of cancer patients. Methods We analyzed colorectal cancer cases for their expression status of POSTN in tumor stroma using immunohistochemistry and correlated the expression status with clinicopathological and molecular features. Results High level of POSTN expression in tumor stroma was closely associated with tumor location in proximal colon, infiltrative growth pattern, undifferentiated histology, tumor budding, luminal necrosis, and higher TNM stage. High expression status of POSTN in tumor stroma was found to be an independent prognostic parameter implicating poor 5-year cancer-specific survival and 5-year progression-free survival. Conclusions Our findings suggest that POSTN overexpression in tumor stroma of colorectal cancers could be a possible candidate marker for predicting poor prognosis in patients with colorectal cancers.